2000
DOI: 10.1046/j.1365-2265.2000.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated insulin‐like growth factor binding protein‐1 with insulin resistance in hyperthyroidism

Abstract: We conclude that in hyperthyroidism thyroid hormones directly increase fasting IGFBP-1 concentration but acute regulation of IGFBP-1 by insulin is normal and that elevated fasting phosphorylated IGFBP-1 concentration is associated with insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2001
2001
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…Smaller studies supported this and showed an increased glucose but also insulin response to an oral glucose tolerance test in patients with subclinical and overt hyperthyroidism [76,77]. When an oral glucose tolerance test is repeated in patients with subclinical or overt hypothyroidism interestingly again glucose and particularly insulin levels are raised supporting insulin resistance under hyperthyroid and hypothyroid conditions.…”
Section: Human Datamentioning
confidence: 71%
“…Smaller studies supported this and showed an increased glucose but also insulin response to an oral glucose tolerance test in patients with subclinical and overt hyperthyroidism [76,77]. When an oral glucose tolerance test is repeated in patients with subclinical or overt hypothyroidism interestingly again glucose and particularly insulin levels are raised supporting insulin resistance under hyperthyroid and hypothyroid conditions.…”
Section: Human Datamentioning
confidence: 71%
“…There have been a number of studies examining the effects of thyroid status on serum concentrations of IGF-1 and its binding proteins in patients with thyroid dysfunction (1)(2)(3)(4)6,(19)(20)(21)(22). Main results of these in vivo investigations suggest that there is an increase in serum levels of IGF-1 in patients with hyperthyroidism (1,5,19,21,23), and a decrease of these values in patients with hypothyroidism (1,2,3,6).…”
Section: Introductionmentioning
confidence: 92%
“…There have been a number of studies examining the effects of thyroid status on serum concentrations of IGF-I and its binding proteins in patients with thyroid dysfunction [8][9][10][11][12][13][14][15][16]. Main results of these in vivo investigations suggest that there is an increase in serum levels of IGF-I in patients with hyperthyroidism [8,13,15,17,18], and a decrease of these values in patients with hypothyroidism [8][9][10]12].…”
Section: Introductionmentioning
confidence: 93%